THE EFFECTIVENESS OF THE USE OF A MODEL OF LEARNING SNOWBALL THROWING TOWARDS THE MATHEMATICS LEARNING OUTCOME ON THE STUDENTS - Riri Ratna Anggraini; Uus Kusdinar (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
The research was done because the learning model which is usually applied in SMP Negeri 2 Girimulyo still tends to be centered on teachers and makes students passive in the learning process. Snowball Throwing is one of many kinds of teaching and learning strategy which provides opportunities to the students to be actively involved in the class activity. The objectives of this research are (1) to know the diversities in the math learning outcome of the eighth-grade students which are taught using the expository learning strategy in the second semester of SMP Negeri 2 Girimulyo in the academic year of 2015/2016, (2) to know the effectiveness of the cooperative learning strategy type Snowball Throwing towards the expository learning strategy to the eighth-grade students in the second semester of SMP Negeri 2 Girimulyo in the academic year of 2015/2016. This research used the quantitative research method. The population of the research was the eighth-grade students in the second semester of SMP Negeri 2 Girimulyo in the academic year of 2015/2016. To obtain the sample, this research used the random sampling technique. As the sample, this research managed the VIII B class as the Experiment Class and VIIIA as the Controlled Class. A test was applied for the data collecting technique of this research. To calculate the instrument validity and reliability, this research used the product-moment correlation and the Alpha formula. The data analyzing the technique of this research are the t-test, the normality test used the Chi-Quadrate formula, and homogeneity test used the Bartlett test. Based on the research findings at the 5% significance level and a degree of freedom of 61, thus the accumulations are (1) ttable= 1,6702 and tcal= 6,4198. It collected tcal>ttable so H0 is rejected. Henceforward, there are diversities in the math learning marks of the students who were taught using the cooperative learning strategy type Snowball Throwing towards those which were taught using the expository learning strategy. (2) ttable= 1,6702 and tcal= 6,4198, collected tcal>ttable so H0 is rejected. To put it briefly, the cooperative learning strategy type Snowball Throwing is more effective than the expository learning strategy towards math learning marks.